Campus regenerative design supported by university Wi-Fi connections. (June 2019) - Mangrich, Camila Poeta; Pavan, Luis Henrique; Gomes, Fernanda; Oliveira, Lucas; Kos, Jose; Martina, Jean Everson
A 60-year-old Brazilian university campus reflects its development actions throughout history. The degradation of its water streams and automobiles prioritization has significantly impacted the ecosystems' resilience and the university's activities. This article explores data analytics and visualization of Wi-Fi authentication processes, whose data have been stored in the last 10 years. This noteworthy connections database is a powerful tool, still overlooked due to the remarkable risks for users' privacy. Brazil has followed 2018 European regulations to protect data privacy, when working with personal data. Therefore, we present an anonymization process that prevents one to identify and distinguish a subject within a set of subjects of the database. Three studies illustrate our examination of data potential to understand the university's dynamics. These inquiries present relevant contributions to the process of planning and implementing campus green areas at the rivers' edges, pedestrian and cycle paths, and places to facilitate interdisciplinary encounters.